2010
DOI: 10.1002/jbmr.313
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic effects of transforming growth factor β on bone morphogenetic protein–induced osteoblast differentiation

Abstract: Bone morphogenetic proteins (BMPs) exert an important role in skeletal development, adult bone homeostasis, and fracture healing and have demonstrated clinical utility for bone regeneration. However, BMPs fall short as regenerative agents because high doses need to be used to obtain therapeutic effects. Determining the molecular mechanisms controlling BMP-induced bone formation may lead to the development of more effective BMP-based therapies. To identify kinases mediating BMP-induced osteoblast differentiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
74
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 53 publications
3
74
0
1
Order By: Relevance
“…61 TGF mainly recruits osteoblast precursors. 62 While some other researchers have tried to release single growth factors from scaffolds, the process of bone regeneration requires multiple growth factors working together to promote the activity of osteogenic-related cells. 63,64 The prolonged release of growth factors from PRF may provide proliferation and differentiation stimuli for BMSCs to promote bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…61 TGF mainly recruits osteoblast precursors. 62 While some other researchers have tried to release single growth factors from scaffolds, the process of bone regeneration requires multiple growth factors working together to promote the activity of osteogenic-related cells. 63,64 The prolonged release of growth factors from PRF may provide proliferation and differentiation stimuli for BMSCs to promote bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies showed biphasic effects of TGF-β on BMP in which TGF-β1, in addition to its action as an inhibitor, could enhance osteoblast differentiation induced by BMP through reducing the negative feedback loop mediated by noggin 26 . This might be useful in improving fracture healing.…”
Section: Discussionmentioning
confidence: 99%
“…The TGF-b-Smad signaling pathway is the most important intracellular signal transduction medium. Smad 2/3 can activate a large number of target genes such as collagen I, cell cycle regulator p15, and p21, among others (De Gorter et al, 2011), as well as cause cell gathering and osteogenesis (Bharadwaj et al, 2013;Gao et al, 2013;Knight and Hankenson, 2013). In this study, though single application of TGF-b failed to result in MSC transformation, strengthened late-stage osteogenesis and cell proliferation abilities were observed under combined use of TGF-b.…”
Section: Discussionmentioning
confidence: 52%